2019
DOI: 10.1088/1757-899x/541/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of spodumene mineral in granitic rocks from South Kalimantan - Indonesia by potassium sulphate

Abstract: The decomposition behaviour of spodumene mineral in granitic rock from Kalimantan Indonesia by using potassium sulphate has been studied in this research. The granitic rock from Kalimantan is indicated to contain spodumene mineral. The sspodumene is one of the main minerals which contains lithium. The purpose of this study is to decompose the α-spodumene mineral in the granitic rock of Kalimantan to β-spodumene which is subsequently easier to be dissolved in water. In this study, the decomposition of α-spodume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Batuan mineral yang mengandung Lithium ditemukan dalam bentuk graphite, tanah laterit-saprolit, dan α-spodumen. Batuan ini ditemukan dibeberapa tempat mulai dari Sulawesi selatan [5], Sulawesi tengah [6], Kalimantan [8], dan Jawa tengah [7]. Lithium dalam konsentrasi yang tinggi sampai dengan 5% dan layak ditambang ditemukan diMekongga, Samaturu, Kolaka, sulawesi selatan dengan luas areal 11 Ha dan kedalaman sampai 13 meter.…”
Section: Sumber Daya Alam Lithium Dalam Bentuk Batuan Mineralunclassified
“…Batuan mineral yang mengandung Lithium ditemukan dalam bentuk graphite, tanah laterit-saprolit, dan α-spodumen. Batuan ini ditemukan dibeberapa tempat mulai dari Sulawesi selatan [5], Sulawesi tengah [6], Kalimantan [8], dan Jawa tengah [7]. Lithium dalam konsentrasi yang tinggi sampai dengan 5% dan layak ditambang ditemukan diMekongga, Samaturu, Kolaka, sulawesi selatan dengan luas areal 11 Ha dan kedalaman sampai 13 meter.…”
Section: Sumber Daya Alam Lithium Dalam Bentuk Batuan Mineralunclassified
“…For spodumene, Hayes et al discussed the roasting of spodumene with gypsum and limestone at 1000–1150 °C for 2–3 h. Setoudeh et al , mainly focused on the effect of mechanical milling on the phase development during the roasting of spodumene–Na 2 SO 4 mixtures, where lithium was converted into water-soluble LiNaSO 4 . Moreover, previous researches have established the process conditions and the mechanism of the roasting of spodumene with K 2 SO 4 . Zelikman et al reported that the roasting was carried out at 920–1150 °C in practice, where α-spodumene was converted into β-spodumene which entered the substitution reaction with K 2 SO 4 . A large excess of K 2 SO 4 was required to form lithium sulfate due to the reversible reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers are exploring alternative processes to overcome the mentioned challenges in extraction of Li from minerals. , One of these is the use of potassium sulfate for reaction with α-spodumene at elevated temperature. , This process was first developed and patented by Wadman. , and it involves roasting α-spodumene with potassium sulfate, resulting in the formation of water-soluble lithium sulfate species and leucite (KAlSi 2 O 6 ) , (reaction ). …”
Section: Introductionmentioning
confidence: 99%
“…It is claimed that heating of potassium sulfate close to its melting point leads to the exchange of potassium with lithium in the β-spodumene structure. , The large difference in the cation radius between lithium (0.78 Å) and potassium (1.33 Å) necessitates the process to be carried out at high temperature . Lower levels of impurities in the water leach liquor and the application of the main byproduct (leucite) as a slow release fertilizer warrant further investigation of the potassium sulfate process as an alternative to the conventional extraction of lithium from spodumene.…”
Section: Introductionmentioning
confidence: 99%